Optimizing the operation release policy using charged system search algorithm: A case study of klang gates dam, Malaysia - Latif S.D.; Marhain S.; Hossain M.S.; Ahmed A.N.; Sherif M.; Sefelnasr A.; El?shafie A. (MDPI AG, 2023)
algorithm; optimization; performance assessment; policy implementation; policy making; reservoir; water demand; water management; water planning; water resource; Malaysia